EFFECT OF WORK EXPERIENCE, COMPETENCE AND INDEPENDENCE ON AUDIT QUALITY WITH ETHICS - Yudha Adi Prakasa; Elvin Bastian; Dadan Ramdhani (STKIP Singkawang, 2023)
This study aims to examine the effect of work experience, competence and independence on audit quality with ethics as a moderating variable. The object of research is the Internal Control Unit (SPI) in the Work Area of Inspectorate IV (Dikti Dikti, Inspectorate General of the Ministry of Education, Culture, Research and Technology) with a total sample of 164 people. Data analysis used moderator regression analysis which was processed with SPSS. Based on the results of the study, it was found that experience had a positive and significant effect on audit quality. Competence has a positive and significant effect on audit quality. Independence has no effect on audit quality. Audit ethics has a positive moderating effect on the relationship between experience and audit quality. Audit ethics does not moderate the relationship between competence and audit quality. Audit ethics has a positive moderating effect on the relationship of independence to audit quality.